1999
DOI: 10.1103/physrevb.59.14282
|View full text |Cite
|
Sign up to set email alerts
|

Positron diffusion in solid and liquid metals

Abstract: We made a systematic study of the diffusion of positrons in several liquid and solid metals with a vertical positron beam. Several interesting effects have been observed by studying the line shape parameter S, the fraction of positronium formed at the surface, and the diffusion length of positrons in liquids. The S parameter and the fraction of positronium created and released at the surface ͑F parameter͒ were measured as a function of temperature in the solid and liquid phases of Ga, Bi, Na, Sn, In, and Pb. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…From Fig.2, it is seen that eq. (5) is consistent with experimental results [15]. Now, we recall that the electro-hydrodynamic stress tenser S el .…”
Section: The Hedgehog-like Density Fluctuation and The Positron Diffusupporting
confidence: 90%
See 2 more Smart Citations
“…From Fig.2, it is seen that eq. (5) is consistent with experimental results [15]. Now, we recall that the electro-hydrodynamic stress tenser S el .…”
Section: The Hedgehog-like Density Fluctuation and The Positron Diffusupporting
confidence: 90%
“…The divergence of electical stress S el defines a local force density f which we write as Positron diffusion length versus temperature in the solid and liquid In and Pb metals. Open circles and solid circles correspond to experimental data points of In and Pb metals [15]. A dotted line is fitted one [23].…”
Section: The Hedgehog-like Density Fluctuation and The Positron Diffumentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an important idea of Kleman and Sadoc [6], it has been proposed that the parameter ρ(r,u) in two-dimensional and three-dimensional metallic liquids and glasses is specified by rigid-body rotation, which are related to gauge fields of SO(3) symmetry for S 2 and SO(4) symmetry for S 3 , respectively [6,7], one(I,K) of the present authors [8][9][10][11][12][13] has introduced the effective Lagrangian in the gauge-invariant formula with spontaneous symmetry breaking for two dimensional and three dimensional metallic liquids and glasses, and has discussed the origin of the boson peak, the glass transition, and the viscosity of the supercooled metallic liquids. Gramsh et al [14,15] have observed very different behaviours of the diffusion length L + of positrons in liquid and solid metals. That is, on melting L + decreases remarkably, and in the liquid phase, L + increases with temperature.…”
mentioning
confidence: 97%
“…One(I.K) of the present authors [17,18] proposed a qualitative explanation for the increase with temperature of the positron diffusion length in liquid metals. In this study, we will analyze the positron diffusion length date in the liquid phase of In metal of Gramsch et al [15] from the view point of the restoration of the spontaneously broken density around the positron [17,18].…”
mentioning
confidence: 99%